2016
DOI: 10.1039/c5bm00197h
|View full text |Cite
|
Sign up to set email alerts
|

Shape control of mesoporous silica nanomaterials templated with dual cationic surfactants and their antibacterial activities

Abstract: Mesoporous silica nanomaterials of different shapes (film, platelet, sphere, rod) were synthesized simply by tuning the mole ratio of dual cationic surfactant templates, cetyltrimethylammonium bromide (CTAB) and tetrabutylammonium iodine (TBAI). The film showed the most potent antibacterial activities against mycobacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 37 publications
(33 reference statements)
1
23
0
Order By: Relevance
“…[25][26][27] Hebalkar et al 28 reported the synthesis of bi-functional silica particles through a simple wet chemical method by attaching titania and silver nanoparticles onto the surface of silica particles in a controlled way to form a core-shell structure, and their investigations indicated that the silica surface exhibited the efficient photo-catalytically self-cleaning and antibacterial activities. A new strategy for the preparation of mesoporous silica materials with different shapes was developed by Hao et al, 29 and they found that the antibacterial activity of these mesoporous silica materials was dependent on their shapes. Qiu et al 30 reported an electrostatic self-assembly method to prepare core-shell structural antimicrobial nanoparticles composed of silica and polyacrylamide and found that the resultant nanoparticles showed a stable and high antibacterial activity toward both S. aureus and E. coil.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Hebalkar et al 28 reported the synthesis of bi-functional silica particles through a simple wet chemical method by attaching titania and silver nanoparticles onto the surface of silica particles in a controlled way to form a core-shell structure, and their investigations indicated that the silica surface exhibited the efficient photo-catalytically self-cleaning and antibacterial activities. A new strategy for the preparation of mesoporous silica materials with different shapes was developed by Hao et al, 29 and they found that the antibacterial activity of these mesoporous silica materials was dependent on their shapes. Qiu et al 30 reported an electrostatic self-assembly method to prepare core-shell structural antimicrobial nanoparticles composed of silica and polyacrylamide and found that the resultant nanoparticles showed a stable and high antibacterial activity toward both S. aureus and E. coil.…”
Section: Introductionmentioning
confidence: 99%
“…Film‐, platelet‐, sphere‐, and rod‐like MS NPs synthesized by varying the mole ratio of cationic surfactant templates, CTAB and tetrabutylammonium iodide (TBAI), were developed by Yan and co‐workers . The release profiles of CTAB and TBAI from differently shaped materials were determined by suspending equal quantities of each material in PBS (pH 7.4) over 48 h. Colony counting antimicrobial test was used to evaluate MS behavior against M. smegmatis strain mc 2 651.…”
Section: Ms In Antibacterial Applicationsmentioning
confidence: 99%
“…This was attributed to the properties of the formed nanocomposites with a variable AgNPs loading, which can significantly improve the dispersion and stability of the deposited AgNPs and enhance their bacteria binding capture efficiency [48]. Dong's group proposed the use of magnetic Janus mesoporous silica nanoparticles (MSNs) with hexadecyltrimethylammonium bromide (CTAB) loading, used both as a soft cationic template for mesoporous silica synthesis and anti-bacterial agent for bacterial elimination, and functionalized with amine groups, as nonselective ligands to bind both Gram-positive and Gram-negative bacteria via electrostatic attraction [53], as anti-bacterial drug [54]. In this way, the mesoporous silica body enhanced bacterial capture, due to its large surface, while the exposed Fe 3 O 4 head maintained the strong paramagnetic property for bacterial separation [49].…”
Section: Static Janus Magnetic Particles For (Bio)sensingmentioning
confidence: 99%